2009
DOI: 10.1093/jxb/erp221
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 is a negative regulator of ABA responses in Arabidopsis

Abstract: Receptor for Activated C Kinase 1 (RACK1) is viewed as a versatile scaffold protein in mammals. The protein sequence of RACK1 is highly conserved in eukaryotes. However, the function of RACK1 in plants remains poorly understood. Accumulating evidence suggested that RACK1 may be involved in hormone responses, but the precise role of RACK1 in any hormone signalling pathway remains elusive. Molecular and genetic evidence that Arabidopsis RACK1 is a negative regulator of ABA responses is provided here. It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 70 publications
5
109
0
1
Order By: Relevance
“…All three Arabidopsis RACK1s are detected in ribosomes Giavalisco et al, 2005;Carroll et al, 2008;Piques et al, 2009;Turkina et al, 2011;Hummel et al, 2012;Carroll, 2013), functionally complement a CPC2/RACK mutant of yeast, and interact with eIF6 (Guo et al, 2011a). Interestingly, single and multiple RACK1 mutants cause a variety of developmental abnormalities and enhance responsiveness to abscisic acid (ABA) (Guo et al, 2009;Guo et al, 2011b). Double mutants of rack1a rack1b are hypersensitive to anisomycin, an inhibitor of peptide elongation and display slightly reduced levels of 80S ribosomes under normal growth conditions and following ABA treatment (Guo and Chen, 2008).…”
Section: Rack1 a Ribosome Interacting Playermentioning
confidence: 99%
“…All three Arabidopsis RACK1s are detected in ribosomes Giavalisco et al, 2005;Carroll et al, 2008;Piques et al, 2009;Turkina et al, 2011;Hummel et al, 2012;Carroll, 2013), functionally complement a CPC2/RACK mutant of yeast, and interact with eIF6 (Guo et al, 2011a). Interestingly, single and multiple RACK1 mutants cause a variety of developmental abnormalities and enhance responsiveness to abscisic acid (ABA) (Guo et al, 2009;Guo et al, 2011b). Double mutants of rack1a rack1b are hypersensitive to anisomycin, an inhibitor of peptide elongation and display slightly reduced levels of 80S ribosomes under normal growth conditions and following ABA treatment (Guo and Chen, 2008).…”
Section: Rack1 a Ribosome Interacting Playermentioning
confidence: 99%
“…Most of what we know comes from physiological analysis of rack1 mutants. Rack1 loss of function mutants display various developmental defects, specifically slow growth, dwarfism, and seedling-lethality in rack1a rack1b rack1c triple mutants (Chen et al, 2006;Guo and Chen, 2008;Guo et al, 2009). The rack1 mutants are less sensitive to gibberellic acid and hypersensitive to abscisic acid and show an mRNA expression profile reminiscent of ABA application (Guo et al, 2011).…”
Section: Rack1mentioning
confidence: 99%
“…8,9 Similar to mammalian RACK1, plant RACK1 interacts with a large group of proteins 10,11 and is involved in diverse biological processes, ranging from seed germination, leaf and root development to flowering, 8,12 and is also involved in responses to plant hormones, 8,13 and biotic and abiotic stresses. [13][14][15] At the molecular level, RACK1 protein is associated with ribosomes [16][17][18] and is involved in the regulation of protein translation 18 and miRNA abundance. 19 It is less clear how RACK1 is able to participate in so many different biological processes.…”
mentioning
confidence: 99%
“…For example, the transcription of RACK1 is suppressed by the plant stress hormone abscisic acid (ABA). 13 It was suggested that such transcriptional regulation likely contributes to RACK1's negative regulation of ABA responses in the ABA-mediated inhibition of seed germination, early seedling development, and ABA-induced gene expression. 13 More recently, it was demonstrated that RACK1 is also regulated at the post-translational level.…”
mentioning
confidence: 99%
See 1 more Smart Citation